THE EUROPEAN UNION DISTINCTIVENESS: A CONCEPT OF THE RULE OF LAW - Adnan Mahmutovic; Helza Nova Lita (Diponegoro Law Review, 2021)
This paper discusses the distinctiveness of the European Union with focus on the Rule of Law and its importance for the EU integration process. Rule of Law is a notion that is very frequently used, but at the same time quite controversial as it is not so easy always to reach generally accepted meaning. Therefore, this paper provides a analysis of the EU Rule of Law  as multidimensional legal principle gravitating between values and principles. The paper acknowledges that a concept of the EU rule of law can be the subject of diverse interpretations and implementation. High-ranking government officials of a two EU member states, Poland and Hungary, have argued recently that a concept of the EU rule of law lacks well-defined rules and remains the subject of much debate. Therefore, the paper provides for better understanding of the concept itself within the specific supranational legal environment. Also, the paper argues that the future of the EU and its integrations depends largely on the respect of the rule of law that remains to be a core and the element of unity within Europe’s legal space. The relationship between the principles and values upon which the EU is founded remain close and interrelated. The EU Rule of law with all its distinctiveness can be concluded with certainty that it reflects a specific character and nature of the EU legal system.